(untitled) (Ukrainian Journal of Ophthalmology, 2024)
Purpose. The purpose of this research was to measure lens posterior cortex thickness and compare it between Chornobyl ex-clean-up workers and healthy individuals to determine whether Chornobyl ex-clean-up workers have a higher prevalence of posterior cortex cataract. Methods. The study was conducted on 32 eyes of healthy, non-exposed individuals, 32 eyes of individuals who worked only in Chornobyl City, and 16 eyes of individuals who worked on the roof of the reactor. All measurements were performed using a Heidelberg Anterion device. Statistical analyses were performed using Jamovi statistical software. Results. The results showed that those who had worked on the roof of the reactor had a significantly higher percentage of their lens occupied by the posterior cortex (median 17.3%, IQR 15.5–18.5%) compared to both the controls and city workers. Therefore, they also have a higher prevalence of posterior subcapsular cataracts (p<0.001). Conclusion. Exposure to increased radiation doses can cause alterations in various body structures, including the lens. Numerous studies have posited that heightened radiation exposure can induce substantial alterations in ocular structural integrity. Conversely, other studies have yielded results that exhibit higher degrees of uncertainty and ambiguity.